Enhanced thermal and electrical properties of hybrid polymer composites containing Al2O3 microspheres and nanowires. Issue 21 (1st November 2022) - Choi, Junhyeok; Song, Kiho; Kim, Jong-Il; Im, Won Bin; Ahn, Changui
Abstract: Thermal interface materials efficiently transfer heat from high-temperature electronic devices to heat management components to alleviate the overheating that deteriorates component lifetimes of electronic devices. Recently, high-performance polymer composites, made of polymer matrices and thermally conducting fillers, have been actively researched due to their low densities and controllable properties. However, the conventional polymer composites produced by mixing methods of homogeneous fillers have significantly low percolation and poor heat dispersion, which afford reduced mechanical and thermal performances. Herein we propose a strategy for fabricating epoxy composites that provide good electrical insulation and enhanced thermal conductivity using a combination of heterogeneous Al2 O3 fillers. The epoxy composites were prepared by using a hybrid filler system comprising microspheres and nanowires, which were fabricated by spray drying and hydrothermal methods, respectively. The use of these two filler components produces a continuous network of fillers throughout the polymer matrix. The thermal conductivity of the hybrid composite is enhanced by 107.9% compared to that of the composite containing only microspheres at the same filler loading (30 wt%). Additionally, the epoxy composites produced with the hybrid filler system provide enhanced electrical insulation (with a dielectric constant of 3.5 at 1 kHz). This hybrid composite approach has the potential to be applied with a wide range of polymers and fillers for use in diverse applications (e.g., wearable devices and electrical vehicles).